Effect of fermented Rosa roxburghii Tratt fruit juice on gut microbiota in a dextran sulfate sodium-induced colitis mouse model - Yunyang Zuo; Haoxiang Xu; Dandan Feng; Yuanyuan Shi; Jiuchang Li; Maoyang Wei; Ling Wang; Yulong Zhang; Ping Hu (Food Science and Human Wellness)
This study mainly investigated the regulatory effect of Rosa roxburghii Tratt fruit juice fermented by Lacticaseibacillus paracasei SR10-1 (LAB-RRTJ) on modulating gut microbiota in dextran sulfate sodium (DSS)-induced ulcerative colitis in mice. Compared to control group, DSS induction decreased body weight of mice, indexes of Shannon, Simpson, Chao1 and Faith_pd, and increased disease activity index (DAI) and levels of interleukin 1β (IL-1β), IL-6, tumor necrosis factor α (TNF -α) and interferon-γ (IFN-γ); And this induction also led to an increase in Proteobacteria, Verrucomicrobia and Actinobacteria at phylum level, harmful bacterial species richness at genus level, and relative richness of S. sciuri, Desulfovibrio C21_c20, R. gnavus and Akkermansia muciniphila at species level, and a decrease in Firmicutes at phylum level and relative richness of B. acidifaciens in mice. LAB-RRTJ increased body weight of mice with DSS induced ulcerative colitis (UC) and indexes of Shannon, Simpson, Chao1 and Faith_pd, reduced DAI and the content of four inflammatory factors and improved gut microbiota imbalance in DSS induced UC mice. Besides, the number of operational taxonomic units (OTUs) increased, α-diversity and β-diversity were restored and similar to those in mice in the control group after LAB-RRTJ treatment. Compared with the positive drug treatment group, LAB-RRTJ has a better effect on regulating gut microbiota diversity in colitis mice. Correlation analysis showed that inflammatory factors were positively correlated with harmful bacteria and negatively correlated with beneficial bacteria which commonly found in some colitis mice. Taken together, our study demonstrated that LAB-RRTJ could alleviate DSS-induced colitis in mice through the modulation of inflammatory cytokines and gut microbiota composition.